PENGARUH KETELADANAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP KEDISIPLINAN SISWA DI SMP PATRA DHARMA 2 BALIKPAPAN - Muhammad Ziidan Asy - Syaddad; Iskandar Yusuf (STKIP Subang, 2026)
This study aims to determine the influence of Islamic Religious Education Teachers on student discipline at Patra Dharma 2 Junior High School Balikpapan. Islamic Religious Education Teachers have a strategic role in shaping the character of students through example, habituation, guidance, and instilling Islamic values in daily life. This study uses a quantitative approach with an independent variable (X), namely Islamic Religious Education Teachers, and a bound variable (Y), namely student discipline. The research population was all students of SMP Patra Dharma 2 Balikpapan, while the sampling technique used Simple Random Sampling. Data was collected through a questionnaire with a Likert scale of four options that had met the validity and reliability tests. Data analysis was carried out using IBM SPSS Statistics through validity tests, reliability tests, normality tests, simple linear regression analysis, t-tests (partial), and determination coefficients (R²). The results of the study show that Islamic Religious Education Teachers have a positive and significant effect on student discipline. This is shown by the value of the correlation coefficient (R) of 0.613 which shows a strong relationship between the two variables. The value of the determination coefficient (R²) of 0.376 shows that Islamic Religious Education Teachers contribute 37.6% to student discipline, while 62.4% are influenced by other factors outside the study. The results of the t-test obtained a significance value of 0.001 (<0.05), so that the alternative hypothesis (Hₐ) was accepted and the null hypothesis (H₀) was rejected. Thus, it can be concluded that Islamic Religious Education Teachers have a positive and significant influence on student discipline at Patra Dharma 2 Balikpapan Junior High School. These findings show that the role of teachers in the learning process is an important factor in shaping the discipline character of students in the school environment.